Theoretical study of the spin-hamiltonanian of a complez with pentavalent molybdeum - Foglio, Mario (Comisión Nacional de Energía Atómica. Instituto Balseiro (Argentina), 1965)
Fil: Foglio, Mario Comisión Nacional de Energía Atómica; Argentina